An introduction to rhetorical communication - McCroskey, James C. (Allyn and Bacon, 1997)
This seventh edition offers a true integration of rhetorical theory and social science approaches to public communication. Key Topics: This highly successful introduction to the field guides readers through message planning and presentation in an easy step-by-step process. All in all, this book provides readers with a solid grounding in the rhetorical tradition and the basis for developing effective messages.